2016
DOI: 10.1152/ajprenal.00208.2015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression of the extracellular calcium-sensing receptor in the mouse, rat, and human kidney

Abstract: The calcium-sensing receptor (CaSR) was cloned over 20 years ago and functionally demonstrated to regulate circulating levels of parathyroid hormone by maintaining physiological serum ionized calcium concentration ([Ca(2+)]). The receptor is highly expressed in the kidney; however, intrarenal and intraspecies distribution remains controversial. Recently, additional functions of the CaSR receptor in the kidney have emerged, including parathyroid hormone-independent effects. It is therefore critical to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 44 publications
4
58
0
Order By: Relevance
“…In the kidney, CaSR is well-known for regulating calcium secretion and absorption in renal tubules [4]. However, accumulating evidence indicates that CaSR is expressed in glomeruli as well, including mesangial cells and podocytes [5]. Observations from our group and others show that CaSR is expressed in mesangial cells and regulates cell proliferation [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…In the kidney, CaSR is well-known for regulating calcium secretion and absorption in renal tubules [4]. However, accumulating evidence indicates that CaSR is expressed in glomeruli as well, including mesangial cells and podocytes [5]. Observations from our group and others show that CaSR is expressed in mesangial cells and regulates cell proliferation [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…CaSR is expressed in various renal cell types in the distal nephron (Graca et al . ). In the present study, the vitamin D/hypercalcaemia‐induced increase in ET‐1 expression was restricted to DCT, CNT and CCD, and none occurred in TAL, despite the much higher expression of CaSR in medullary thick ascending limb and cortical thick ascending limb than in any other tubular segment (Loupy et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Graca et al . ). Moreover, ET‐1 mRNA expression did not significantly differ between mice expressing an activating mutation of Casr and wild‐type mice.…”
Section: Discussionmentioning
confidence: 97%
“…In the kidney, CaSR senses changes in both urine and serum calcium levels, which indicates a direct role in renal calcium handling (30). In the collecting duct, CaSR is expressed in intercalated cells and principal cells of the collecting duct (53) and is activated by luminal calcium. Specifically, in principal cells, CaSR is colocalized with the AQP2 water channel (30, 53, 54).…”
Section: Discussionmentioning
confidence: 99%
“…In the collecting duct, CaSR is expressed in intercalated cells and principal cells of the collecting duct (53) and is activated by luminal calcium. Specifically, in principal cells, CaSR is colocalized with the AQP2 water channel (30, 53, 54). Several in vitro and in vivo studies, including those in humans, have suggested that CaSR signaling inhibits vasopressin‐induced trafficking and expression of AQP2 (22, 2426, 28, 5558).…”
Section: Discussionmentioning
confidence: 99%